Spin‐Echo Electron Paramagnetic Resonance (EPR) Spectroscopy of a Pore‐Forming (Lipo)Peptaibol in Model and Bacterial Membranes. Issue 5 (17th May 2013) - Dzuba, Sergei A.; Raap, Jan
Abstract This review compiles the unusual structural and dynamic peculiarities of trichogin GA IV and its analogs in lipid bilayers. Different electron spin echo (ESE) spectroscopic techniques were employed to study a set of spin‐labeled analogs of trichogin GA IV in model and natural membranes. Pulsed electron‐electron double resonance (PELDOR) method enabled the elucidation of the peptide conformation, while the ESE envelope modulation (ESEEM) technique was applied to study the insertion of the site‐specifically spin‐labeled peptide into the core of the membrane. The latter technique was also used to examine the water accessibility for peptide‐attached spin labels at different levels of membrane depth. Finally, it will be shown that measurement of the ESE decays at different temperatures reveals molecular information on the mobility of the transmembrane lipopeptide aggregate. The experimental results are discussed in terms of the antibiotic and toxic activities of trichogin GA IV.